Efeitos da estimulação sensório motora oral sobre a sucção não-nutritiva de recém-nascidos pré-termo - Yamamoto, Raquel Coube de Carvalho (2008)
To verify the oral motor sensorial stimulation effects on the non-nutritive sucking, by comparing the aspects and development of the non-nutritive sucking function in preterm infants in a group which has received oral motor sensorial stimulation towards another which has nor received any kind of stimulation. Method: A 20 preterm infants sample randomized into control and experimental groups. The following were considered: sucking strength; sucking rhythm; presence of the three adaptative aspects; and sucking blocks (total sucking number and time of, total sucking pause and frequency). Result: Both control and experimental groups were homogeneous concerning their general characteristics and results at the first evaluation. The differences could be observed from the second to the third evaluations, where the experimental group has presented better results related to strength, rhythm and sucking frequency. For most results there was no statistically significant result. Conclusion: The preterm infants who received the stimulation program presented an improvement in the sucking aspects and in the non-nutritive sucking function performance.